2020
DOI: 10.15611/pn.2020.2.07
|View full text |Cite
|
Sign up to set email alerts
|

Technical efficiency of dairy farms in 2008-2017

Abstract: The aim of the study was to determine the technical efficiency of farms specialising in milk production (type 45) using the DEA method. The research covered the period 2008-2017. Data for calculations were collected using the indirect observation method based the data from the Polish FADN Cfor2008-2017 as the source of actual data. 11055 dairy farms were included in the study. Dairy farms with fewer than 15 cows were excluded from the study. The DEA method uses an approach that minimizes inputs and the CCR and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The model assumed the sum of revenues from milk sales and processed products, live cattle, balances of subsidies and taxes, with inputs such as agricultural land area, number of dairy cows, yield costs, purchased feed, other direct costs of animal production, maintenance costs of machinery and equipment, energy costs, and amortization costs. In subsequent studies by Świtłyk [43], using the DEA method and the CCR and BCC models and adopting the same set of variables, proved that in the CCR model the highest technical efficiency coefficients were characteristic for large farms, while the lowest scale efficiency coefficients were found for medium-small farms. The highest technical efficiency coefficients for the CCR, BCC and scale efficiency models were recorded on farms with the highest milk yield.…”
Section: Literature Reviewmentioning
confidence: 96%
See 1 more Smart Citation
“…The model assumed the sum of revenues from milk sales and processed products, live cattle, balances of subsidies and taxes, with inputs such as agricultural land area, number of dairy cows, yield costs, purchased feed, other direct costs of animal production, maintenance costs of machinery and equipment, energy costs, and amortization costs. In subsequent studies by Świtłyk [43], using the DEA method and the CCR and BCC models and adopting the same set of variables, proved that in the CCR model the highest technical efficiency coefficients were characteristic for large farms, while the lowest scale efficiency coefficients were found for medium-small farms. The highest technical efficiency coefficients for the CCR, BCC and scale efficiency models were recorded on farms with the highest milk yield.…”
Section: Literature Reviewmentioning
confidence: 96%
“…On the other hand, the lower age of first calving, higher milk yield and higher number of somatic cells were positively correlated with technical efficiency. In the context of Poland, the issue of technical efficiency and productivity of dairy farms was raised in the research, among others, by Świtłyk [42,43], Marzec et al [11], Borecka et al [44] and Adamski [45]. Świtłyk [42], determining the technical efficiency of dairy farms depending on the size of a herd of cows using the DEA and SFA methods, showed that, according to the BCC model, farms with the smallest (<10 cows) and the largest (>40 cows) herds of cows had the most technical efficiency, while in the SFA model the highest technical efficiency coefficients were characteristic of farms with the largest herds of cows ( 30; 40 <40 and >40 cows).…”
Section: Literature Reviewmentioning
confidence: 99%